2016
DOI: 10.1097/md.0000000000004292
|View full text |Cite
|
Sign up to set email alerts
|

The thyroid imaging reporting and data system on US, but not the BRAFV600E mutation in fine-needle aspirates, is associated with lateral lymph node metastasis in PTC

Abstract: The majority of patients with papillary thyroid carcinoma (PTC) have an excellent prognosis, but some show poorer outcomes and would benefit from adjunctive prognostic tools. The B-Raf proto-oncogene, serine/threonine kinase (BRAF)V600E mutation, either based on both its presence or its quantitative measurement, and ultrasound (US) features may serve as a prognostic marker. The aim of this study was to investigate (1) the association between clinical-pathologic prognostic factors and the BRAFV600E mutation fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…The association between US features classified by the thyroid imaging reporting and data system (TIRADS) and cervical LMN was also explored. In a study carried out by Park et al ( 40 ), it was found that the number of suspicious TIRADS US features was associated with lateral LMN in PTC. However, to our knowledge, no previous studies have addressed the relationship between thyroid parenchymal US features and cervical LNM.…”
Section: Discussionmentioning
confidence: 96%
“…The association between US features classified by the thyroid imaging reporting and data system (TIRADS) and cervical LMN was also explored. In a study carried out by Park et al ( 40 ), it was found that the number of suspicious TIRADS US features was associated with lateral LMN in PTC. However, to our knowledge, no previous studies have addressed the relationship between thyroid parenchymal US features and cervical LNM.…”
Section: Discussionmentioning
confidence: 96%
“…Evaluation results for lateral cervical lymph nodes vary the most among physicians, with the reported positive predictive values ranging from 38.5% to 64% according to different levels of experience [10]. Previous research has also focused on US or the pathologic features of the primary thyroid tumor itself, and has reported that a high suspicion US pattern, upper pole location, extrathyroidal extension, presence of calcifications, and central LNM are associated with lateral LNM [19][20][21]. However, such qualitative imaging features are also based on the judgment of the performing physician and therefore, prone to interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
“…PTC with suspicious US features more frequently had lymph node metastasis at diagnosis and recurrence than PTC without suspicious US features [ 32 , 34 ]. Moreover, higher number of suspicious US features were associated with lymph node metastasis in patients with PTC [ 33 ]. In a study by Kwak et al [ 17 ], upper pole location, minimal extrathyroidal extension on US (> 25% contact with the adjacent capsule), and the presence of calcifications were the independent predictors of lateral lymph node metastasis in patients with PTMC.…”
Section: Discussionmentioning
confidence: 99%